Clinical features of Friedreich's ataxia: classical and atypical phenotypes. (17th July 2013) - Parkinson, Michael H.; Boesch, Sylvia; Nachbauer, Wolfgang; Mariotti, Caterina; Giunti, Paola
Abstract: One hundred and fifty years since Nikolaus Friedreich's first description of the degenerative ataxic syndrome which bears his name, his description remains at the core of the classical clinical phenotype of gait and limb ataxia, poor balance and coordination, leg weakness, sensory loss, areflexia, impaired walking, dysarthria, dysphagia, eye movement abnormalities, scoliosis, foot deformities, cardiomyopathy and diabetes. Onset is typically around puberty with slow progression and shortened life‐span often related to cardiac complications. Inheritance is autosomal recessive with the vast majority of cases showing an unstable intronic GAA expansion in both alleles of the frataxin gene on chromosome 9q13. A small number of cases are caused by a compound heterozygous expansion with a point mutation or deletion. Understanding of the underlying molecular biology has enabled identification of atypical phenotypes with late onset, or atypical features such as retained reflexes. Late‐onset cases tend to have slower progression and are associated with smaller GAA expansions. Early‐onset cases tend to have more rapid progression and a higher frequency of non‐neurological features such as diabetes, cardiomyopathy, scoliosis and pes cavus. Compound heterozygotes, including those with large deletions, often have atypical features. In this paper, we review the classical and atypical clinical phenotypes of Friedreich's ataxia.